Wyoming summer - O'Hara, Mary 1885-1980 (Doubleday, 1963)
Documentary novel based on the author's journal describing life on her family ranch--caring for teen-age "dude" boarders, composing music, and recording experiences with people and animals for the background of her novels.
Keywords: O'Hara, Mary -- Homes and haunts -- Wyoming; Geschichte 1900-2000; Alltag, Brauchtum; Authors, American -- Homes and haunts -- Wyoming; Authors, American -- 20th century -- Biography; Ranch life -- Wyoming; Wyoming -- Social life and customs; Biografie